1993
DOI: 10.1002/1097-0142(19930501)71:9<2751::aid-cncr2820710911>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Primary peritoneal carcinoma after prophylactic oophorectomy in women with a family history of ovarian cancer. A report of the gilda radner familial ovarian cancer registry

Abstract: Background. According to previous reports, primary peritoneal carcinoma indistinguishable from primary ovarian adenocarcinoma had developed in five women with a history of familial ovarian cancer who had undergone prophylactic oophorectomy. Methods. The records from the Gilda Radner Familial Ovarian Cancer Registry were reviewed for instances of prophylactic oophorectomy and cases of primary peritoneal carcinoma occurring after prophylactic oophorectomy. Results. From 1981 through July 1992, the Gilda Radner F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
92
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 308 publications
(99 citation statements)
references
References 10 publications
3
92
0
4
Order By: Relevance
“…However, at the time of the diagnosis of PPSC no malignant lesions were found in the fallopian tubes. Furthermore, it has been shown that PPSC has developed after salpingo-oophorectomy (Piver et al, 1993). So, we have concluded that PPSC is a primary tumour and not a metastasis.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, at the time of the diagnosis of PPSC no malignant lesions were found in the fallopian tubes. Furthermore, it has been shown that PPSC has developed after salpingo-oophorectomy (Piver et al, 1993). So, we have concluded that PPSC is a primary tumour and not a metastasis.…”
Section: Discussionmentioning
confidence: 61%
“…Second, the later study also includes 42 BRCA2 carriers (43%), while the incidence in our series is established for BRCA1 carriers who have a higher intrinsic ovarian cancer risk, and this may also be true for PPSC. Other studies neither described procedures nor whether the cases were BRCA1 or BRCA2 mutation carriers (Piver et al, 1993;Rebbeck et al, 2002). Our series of 64 BRCA1 and BRCA2 mutation carriers after salpingo-oophorectomy includes only six BRCA2 carriers (9.4%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is not unexpected in the light of previous studies reporting a low risk of PPC. 27,31,32 In the recent study by Finch et al 33 in women who had undergone SO, the annual risk of PPC was estimated to be 0.217% in BRCA1 carriers and 0.167% in BRCA2 carriers. On the basis of these estimates, less than 1 case would have been expected in our series.…”
Section: Discussionmentioning
confidence: 85%